Islands and Continents : Short Stories by Leung Ping-kwan - Leung, Ping-kwan, 1949- (Book collections on Project MUSE.)
In this kaleidoscope of stories, translated from the Chinese, P.K. Leung, one of Hong Kong's most celebrated literary figures, presents his personal vision of the city, evoking in his inimitable voice the local and international dimensions of this extraordinary place, capturing its poignant ambivalence as a postcolonial territory on the fringe of China.